2024
DOI: 10.3390/coatings14030260
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal and Antiviral Activity of Coatings Containing Zinc Oxide Nanoparticles and Verbascum L. or Formitopsis betulina Extracts and Their Influence on the Quality of Strawberries after Storage

Małgorzata Mizielińska,
Magdalena Ordon,
Weronika Burdajewicz
et al.

Abstract: The goal of this study was to analyze the antifungal and antiviral activity of coatings based on Formitopsis betulina, Verbascum L. and Uncaria tomentosa extracts with ZnO nanoparticles as active compounds. The other purpose was to investigate the impact of polypropylene bags coated with the obtained antiviral/antifungal coatings on the microbial quality/purity of strawberries. The results of this study showed that the analyzed coatings inhibited Candida albicans growth completely. They did not inhibit the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…These findings con-firmed that the E sample exhibited slight activity against Φ6 bacteriophage, in contrast to noncovered film and EZ. Contrary results were observed in the previous research [39], which demonstrated that the coatings containing ZnO nanoparticles and Formitopsis betulina, Verbascum L., or Uncaria tomentosa extracts exhibited the complete reduction in the Φ6 lysate titer compared with the noncovered films. Moreover, the layers containing ZnO nanoparticles without plant extracts were not effective against the phi6 phage.…”
Section: )contrasting
confidence: 99%
See 1 more Smart Citation
“…These findings con-firmed that the E sample exhibited slight activity against Φ6 bacteriophage, in contrast to noncovered film and EZ. Contrary results were observed in the previous research [39], which demonstrated that the coatings containing ZnO nanoparticles and Formitopsis betulina, Verbascum L., or Uncaria tomentosa extracts exhibited the complete reduction in the Φ6 lysate titer compared with the noncovered films. Moreover, the layers containing ZnO nanoparticles without plant extracts were not effective against the phi6 phage.…”
Section: )contrasting
confidence: 99%
“…The previous research demonstrated that active coatings with ZnO nanoparticles also decreased the number of C. albicans cells [21]. However, the coating with the nanofiller completely inhibited the growth of yeast [39]. The 24 h and 72 h of Q-SUN irradiation had a marked influence on the effectiveness of the E and EZ coatings against C. albicans, decreasing their activity.…”
Section: Antimicrobial Properties Analysismentioning
confidence: 95%